BIOMASS OF Eucalyptus globulus IN YOUNG PLANTATIONS IN URUGUAY - Vallejos-Barra, Oscar Santiago; Ibáñez Córdova, Alfredo; Moras, Guillermo; Daniluk-Mosquera, Gustavo; Ponce-Donoso, Mauricio (Floresta, 2020)
Biomass of Eucalyptus globulus in young plantations in Uruguay. In four areas of the western coast of the Oriental Republic of Uruguay (Algorta, Bequeló, Quebracho and Tres Bocas) the aerial biomass of Eucalyptus globulus plantations was quantified with ages between 3 and 9 years. In 20 circular plots of 300 m2, 616 trees were measured, selecting 132 for quantification. In each tree, the biomass of five components was calculated: leaves, green branches, dry branches, stem and total aerial, the latter obtained by adding the previous components. Four allometric functions were adjusted in three scenarios: by location, for total locations and for total locations, but identified by dummy variables. The functions by location presented minimal difference from Akaike information criterion (AIC), so that in all cases this type of function was selected. The average annual increase in biomass was obtained, with average values for all the localities of 1.18 ± 0.45, 1.08 ± 0.18, 0.58 ± 0.22, 11.24 ± 1.86 y 14.20 ± 2.50 Mg ha-1 year-1 for leaves, green branches, dry branches, stem and total aerial, respectively. An analysis of variance by component identified statistically significant differences in the average annual increase in biomass between locations. The localities with the highest increase were Bequeló and Tres Bocas, followed by Quebracho and Algorta. The analysis of variance incorporated planting density as a covariate, proving to be significant for the components of greater dimensions.